INSETOS AQUÁTICOS COMO BIOINDICADORES DA QUALIDADE DA ÁGUA DO AÇUDE CACHOEIRA II, SERRA TALHADA, PERNAMBUCO - Silva, Amanda Cavalcante; Marques, Samir Emanuel Amaral; Matos, Cláudia Helena Cysneiros; Oliveira, Carlos Romero Ferreira de (Revista Nordestina de Zoologia, 2016)
The biomonitoring of the quality of water resources and the use of biotic indexes for this purpose have been increasingly adopted in several regions. In the present study, the composition of the community of aquatic and semi - aquatic insects associated with macrophytes was evaluated in Cachoeira II, Serra Talhada, Pernambuco - PE, inferring the possible use of these organisms in environmental biomonitoring programs in the region. The collections were carried out from October 2015 to June 2016. In order to obtain the insect samples, aquatic macrophytes were collected with using an aquatic entomological net in four collection stations, using three replicates for each point. The biotic index BMWP (Biological Monitoring Working Party) was applied in order to demonstrate the quality of the water. In addition, insects were classified as functional feeding groups and their degree of tolerance to pollution was determined. Sixty - seven specimens were found, distributed in ten families, with a predominance of predatory and tolerant organisms. The Odonata Coenagrionidae, genus Homeoura, were the most abundant. According to the BMWP index the environment was characterized as being of dubious quality with polluted water present. These results cause concern, since water from the Cachoeira II dam is widely used for supplying the municipality of Serra Talhada-PE and for irrigation. This reinforces the importance of biomonitoring studies and the need for measures to recover and conserve this water body.